Condition Index and Percentage Edibility of Crassostrea madrasensis (Preston) inhabiting the Cochin Harbour - NAIR, N. UNNIKRISHNAN; NAIR, N. BALAKRISHNAN (Fishery Technology, 2017)
Monthly variations in condition index and percentage edibility of the population of oysters, namely, Crassostrea madrasensis (Preston) is reported for males, females and indeterminates for the period October 1981 to September 1982. Condition index and percentage edibility showed more or less similar trend for the total population and also for males, females and indeterminates. The condition index and percentage edibjlity were maximu.m during October 1981 which declined progressively and reached the lowest in Febmary–Masch, 1982. From April it showed steady increase and reached the maximum agam m October 1982 and this coincided with the gonadal cycle in oysters.